Analisis Quality Control Internal Pemeriksaan Sgot dan Sgpt Menggunakan Grafik Levey-Jennings dan Six Sigma di RS X Yogyakarta: Internal Quality Control Analysis of Sgot and Sgpt Examination Using Levey-Jennings Graphics and Six Sigma at X Hospital Yogyakarta - Sulma Hajijatur Ridlwana; Arifiani Agustin Amalia; Yeni Rahmawati (Journal of Health (JoH), 2025)
Quality control (QC) is a process in monitoring and evaluating activity at the analytical stage, quality control aims to monitor accuracy, precision, LeveyJennings graphs, Westgard rules and six sigma to detect errors in laboratory examinations immediately and determine the performance of the laboratory. This research was conducted to find out how the quality control of SGOT and SGPT enzyme examinations is carried out in PKU Muhammadiyah Gamping Hospital laboratory. This research uses a quantitative descriptive research method with a cross sectional approach. The data used in this research was secondary data for daily control of SGOT and SGPT examinations for July-December 2023. The data obtained would be processed using Microsoft Excel by creating a Levey-Jennings graph then evaluated using Westgard rules and calculating the mean, SD, CV, TV values, TE, bias and six sigma Based on the research conducted, it was found that the results of the Levey-Jennings graph for the SGOT and SGPT parameters were not affected by the wetsgard rule. The accuracy and precision values for SGOT and SGPT showed high results. The six sigma value for SGOT examination parameters was 6.5 and for SGPT was 8.2. The six sigma value was included in the world class category with very good laboratory performance.